Consideraciones generales sobre la acción colectiva contenciosa y la solidaridad política a partir de cuatro trayectorias organizacionales - Aranda Andrade, Marco Antonio (El Colegio de México, 2014)
In this research note, we expose some of the ways in which solidarity becomes a contentious political force for collective action within transactions between organizations that are or were part of neozapatismo in Mexico and the Spanish State. From the implementation of a three-dimensional analytical approach that integrates theoretical assumptions about the normative guidelines of collective action, organizational dynamics of collective actors and group processes that have place in each organization and in their alliances space, we analize the processes that lead forms of solidarity among actors involved in an extensive coordination and dispute space, traversed by multiple political contexts that produce dynamics of exclusion, repression, negotiation and integration.